TINJAUAN YURIDIS TINDAK KEKERASAN ORANG TUA TERHADAP ANAK - Gomgom TP Siregar; Irma Cesilia Syarifah Sihombing (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
Legal protection for children is all efforts made to create conditions so that each child can exercise his rights and obligations for the development and growth of children naturally, both physically and mentally, social development. Children often become physical victims in the household, physical violence experienced by children is mostly carried out by those closest to the child and many factors cause physical violence against children by parents.To answer this problem, the method used in this research is normative juridical, this method was chosen to find out how the role of legislation regarding legal protection for victims of domestic violence. This type of research uses normative juridical research. Collecting data using literature study method. Victims of violence perpetrated by parents must receive legal protection from a legal, sociological and material perspective. There are several factors that cause violence against children, including economic, environmental and child factors. To prevent physical violence against children, it is necessary to have control, either from the government or from the child's family or parents. One form of overcoming violence against children is to socialize the impact of physical violence against children by parents.